Analisis Peran Kelompok Sadar Wisata Telok Kombal Dalam Mengembangkan Ekowisata Bukit Sumbur Suma - Muhammad Rahmatul Burhan; Mardiah Mardiah (Universitas Muhammadiyah Mataram, 2020)
This research aims to determine the role of Pokdarwis in the development of the Sumbur Suma Hill in Telok Kombal, North Lombok. This research uses the case study method. Focus of the research is to examine the role of Pokdarwis with the role indicators presented by Minztberg: Interpersonal roles, Roles related to information, and the role of decision makers. The main data collection by interview was collaborated with the results of observation and documentation. Data were analyzed using an Interactive Model technique that passes through two types of triangulation (data triangulation and methodological triangulation). In an effort to develop the Sumbur Suma Hill ecotourism, Pokdarwis Telok Kombal has performed its role as it should, although it is still faced with various obstacles. For product development, Pokdarwis plays the role of decision maker. In terms of standardization development, Pokdarwis plays two roles, the role associated with information and the role of decision makers. Then community empowerment, Pokdarwis plays two roles, interpersonal role and decision maker role. The stakeholder part, Pokdarwis has been able to carry out its entire role.